Global Trends in Conservation Agriculture and Climate Change Research: A Bibliometric Analysis - Julio Román-Vázquez; Rosa M. Carbonell-Bojollo; Óscar Veroz-González; Ligia Maria Maraschi da Silva Piletti; Francisco Márquez-García; L. Javier Cabeza-Ramírez; Emilio J. González-Sánchez (Agronomy)
This study provides a bibliometric analysis of global scientific production on Conservation Agriculture (CA) and its relationship with climate change mitigation. Using data from the Scopus and Web of Science databases, the research encompassed 650 articles published between 1995 and 2022. The analysis revealed significant growth in the number of publications over the past three decades, driven by increasing global interest in sustainable agricultural practices. The findings highlight key themes, including no-tillage, soil organic carbon, and greenhouse gas emissions. Collaboration networks were mapped, identifying major contributors, such as the USA, Brazil, and China, alongside thematic clusters emphasizing carbon sequestration and soil management. Results indicate that CA research is increasingly focused on its potential to mitigate climate change, particularly through practices like no-tillage, vegetative cover, and crop rotation. While carbon sequestration has been central to CA research, recent studies have expanded to include nitrous oxide and methane emissions, indicating a broadening conceptual framework. This analysis underscores the importance of CA in addressing climate challenges and offers insights into emerging research areas, such as regional adaptations and the long-term effects of no-till systems. The findings aim to guide future research and policy development in sustainable agriculture and climate mitigation.